Implantación de la contabilidad en el almacén “Camilita" de la ciudad Yantzaza, periodo del 01 de julio al 31 de diciembre del 2019. - Morocho Ordóñez, Carmen Anahí (2020)
This thesis entitled IMPLEMENTATION OF ACCOUNTING IN THE "CAMILITA" STORE OF THE CITY YANTZAZA PERIOD FROM JULY 01 TO DECEMBER 31, 2019, is intended to implement commercial accounting that allows the owner to provide information on the economic and financial situation of your business for proper decision making, through the obtaining of financial statements and the application of financial indicators. To comply with the objectives set out in the thesis project, a plan and manual of accounts was prepared that allowed the classification, codification and description of the assets, liabilities, equity, income and expenses accounts; Auxiliary books were designed and produced that simplified operations at the time of their registration in the daily book such as: purchase, sales, documents receivable, documents payable, deposits, fuel, transportation, payment roles and provisions ; The accounting process was developed starting with the lifting of the initial inventory determining its assets, liabilities and equity, then the initial situation statement was prepared, daily book, ledger , balance sheet, worksheet and obtaining the financial statements where the net income for the year, was reflected as a result of the economic activities carried out by the warehouse in the accounting period from July to December 2019; Finally, the application of financial indicators was carried out that allowed measuring: liquidity, determining that the warehouse is able to meet its short-term obligations and has the necessary resources to develop its operations, the activity indices demonstrated the efficiency in use of its resources and in administrative management, in terms of indebtedness, a financing of the asset of 68% by creditors was reflected and it was evidenced that the equity is insufficient to cover its obligations and, the profitability indicators reflected that the profit obtained is low in relation to the investment made and the expenses incurred by the warehouse. 5 Therefore, it was found that the implementation of accounting and application of financial indicators in the warehouse is of great importance, because through the different accounting records and books, a better control of operations is allowed and thus provides truthful and timely information through its financial statements and the results of the application of indicators, serving as the basis for adequate decision-making by its owner in order to obtain greater benefits through the growth of its business.